Effect of freshwater on plant species diversity and interspecific associations in coastal wetlands invaded by Spartina alterniflora - Dou, Zhiguo; Cui, Lijuan; Li, Wei; Lei, Yinru; Zuo, Xueyan; Cai, Yang; Yan, Rui (Frontiers in Plant Science, 2022)
Plant invasions in coastal wetlands lead to the degradation of native vegetation; the introduction of freshwater in coastal wetlands would prevent the spread of invasive plants and facilitate the restoration of native vegetation. In this study, we evaluated the effects of freshwater on plant communities in the coastal wetlands of Yancheng, China, invaded by Spartina alterniflora Loisel. Two field investigations were conducted in 2008 and 2018 before and after the introduction of freshwater (started in 2011). The characteristics of plant communities were subjected to hierarchical cluster analysis and compared using several diversity indices. In addition, differences in habitat community composition and interspecific relationships of dominant species were analyzed. The results showed that S. alterniflora reduced the overall species diversity in the region. Plant species diversity increased after freshwater was introduced into the study site when compared to the areas without freshwater introduction. The introduction of freshwater caused a shift often changes in the interspecific relationships between Suaeda salsa (L.) Pall. and other species. The intensified invasion of S. alterniflora changed the interspecific relationship of native halophytes from negative to positive. Although freshwater effectively inhibited further invasion of S. alterniflora, it also increased the risk of expansion of the glycophytes in the community. The results of this study highlight the need for early intervention for restoration of coastal wetlands, preservation of biodiversity, and management of plant resources.